Homologs of Breast Cancer Genes in Plants - Trapp, Oliver; Seeliger, Katharina; Puchta, Holger (Frontiers in Plant Science, 2011)
Since the initial discovery of genes involved in hereditary breast cancer in humans, a vast wealth of information has been published. Breast cancer proteins were shown to work as tumor suppressors primarily through their involvement in DNA damage repair. Surprisingly, homologs of these genes can be found in plant genomes, as well. Here, we want to give an overview of the identification and characterization of the biological roles of these proteins, in plants. In addition to the conservation of their function in DNA repair, new plant-specific characteristics have been revealed. BRCA1 is required for the efficient repair of double-strand breaks by homologous recombination in somatic cells of the model plant Arabidopsis thaliana. Bioinformatic analysis indicates that, whereas most homologs of key components of the different mammalian BRCA1 complexes are present in plant genomes, homologs of most factors involved in the recruitment of BRCA1 to the double-strand break cannot be identified. Thus, it is not clear at the moment whether differences exist between plants and animals at this important step. The most conserved region of BRCA1 and BARD1 homologs in plants is a PHD domain which is absent in mammals and which, in AtBARD1, might be involved in the transcriptional regulation of plant development. The presence of a plant-specific domain prompted us to reevaluate the current model for the evolution of BRCA1 homologs and to suggest a new hypothesis, in which we postulate that plant BRCA1 and BARD1 have one common predecessor that gained a PHD domain before duplication. Furthermore, work in Arabidopsis demonstrates that - as in animals - BRCA2 homologs are important for meiotic DNA recombination. Surprisingly, recent research has revealed that AtBRCA2 also has an important role in systemic acquired resistance. In Arabidopsis, BRCA2 is involved in the transcriptional regulation of pathogenesis-related genes via its interaction with the strand exchange protein RAD51.